Pengaruh Metode Bercerita Pada Perkembangan Bahasa Anak Usia Dini: The Effect of Storytelling Method on Early Childhood Language Development - Wahyuni , Annisa; Hasanah, Nur (Prodi Pendidikan Islam Anak Usia Dini Sekolah Tinggi Agama Islam Negeri Mandailing Natal- Sumatera Utara, 2023)
The development of children's language through the linguistic method is the development of children in managing words effectively orally and in writing. The goal is to communicate knowledge and help children to interact with peers and their social environment. The method of telling is one of the efforts in developing language at an early age. For this reason, starting in this research is how to develop early language through the storytelling method, how to develop early language through the storytelling method to answer problems using qualitative descriptive research. The research subjects were teachers and students, data collection techniques, observations, interviews and documentation, the results of the research were developments that had developed for early childhood language development, in the implementation it was optimal in using the storytelling method. Qualitative data analysis is inductive, namely an analysis based on data obtained and developed.